1409PKnown and unknown gene fusion detection capabilities of solid tumour laboratories conducting next generation sequencing in 6 countries. (1st October 2019) - Finucane, S; Haridas, S; Handley, L; Clark, J; Jack, A; Munksted, S
Abstract: Background: Developments in next generation sequencing (NGS) have revolutionized oncogenic biomarker detection, removing the limitations of single-nucleotide polymorphisms (SNPs) to allow for massive parallel sequencing to detect multiple oncogenic gene fusions. We believe NGS testing platforms are not uniform within the current solid tumor lab landscape, with NGS analysis capabilities ranging from SNPs only to SNPs and known gene fusions, potentially missing crucial biomarkers. The objective of this study was to determine the current NGS capability of solid tumor labs to detect unknown fusions. Methods: This study used real-world clinical pathology solid tumor labs data from the United States, United Kingdom, France, Spain, Italy, and Germany that conduct NGS. The Diaceutics proprietary global database of more than 2500 labs was analysed across these markets in Q4 2018 to understand NGS testing capabilities currently available within the routine clinical lab setting. Results: The results of the study are presented in the table. Of the 131 labs in the US performing NGS, only 50 were able to detect fusions. Of those 50 labs, 42 were restricted to using panels designed to detect specific known fusions. Only 8 labs in the US were able to detect unknown fusions. This pattern was reflected in labs surveyed in 5 other countries. Conclusions: Labs are not well equipped to handle the pace of advancement in biomarker testing. While targeted treatments and companion diagnostics usher in a new age of precision medicine in cancer and extend survival times, many labs lack the technology needed to accurately identify emerging gene fusion biomarkers, especially unknown fusions. This results in both confusion among physicians regarding testing adequacy and missed opportunities for improved outcomes among patients. Legal entity responsible for the study: Diaceutics. Funding: Diaceutics. Disclosure: S. Finucane: Full / Part-time employment: Diaceutics. S. Haridas: Shareholder / Stockholder / Stock options, Full / Part-time employment: Diaceutics. L. Handley: Full / Part-time employment: Diaceutics. J. Clark: Shareholder / Stockholder / Stock options, Full / Part-time employment, Officer / Board of Directors: Diaceutics. A. Jack: Shareholder / Stockholder / Stock options, Full / Part-time employment: Diaceutics. S. Munksted: Shareholder / Stockholder / Stock options, Full / Part-time employment: Diaceutics.